2018
DOI: 10.1186/s12913-018-3729-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, course and outcome of patients receiving physiotherapy in primary health care in Norway: design of a longitudinal observational project

Abstract: BackgroundPhysiotherapists (PTs) in primary health care manage patients with large variation in medical diagnosis, age, functional status, disability and prognosis. Lack of knowledge and systematically collected data from patients treated by PTs in primary health care has prompted this longitudinal observational physiotherapy project. This paper aims to describe a method for developing a database of patients managed by PTs in primary health care, with the main purpose to study patients’ characteristics, treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 3 publications
0
39
1
4
Order By: Relevance
“…Reasons for exclusion were reduced cognitive function incapable of giving consent or the PT not being able to reach the next of kin, language barriers for non-Norwegian speaking patients and ethical concerns for patients receiving palliative care. We have previously reported that sex and age distribution of adult and older patients included in FYSIOPRIM were comparable to those not included, although a higher proportion of non-included patients were living in institutions and more often referred because of geriatrics/functional deterioration (14). As a result, our sample may have had better physical performance compared with the broad spectrum of patients receiving home based physiotherapy.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
See 3 more Smart Citations
“…Reasons for exclusion were reduced cognitive function incapable of giving consent or the PT not being able to reach the next of kin, language barriers for non-Norwegian speaking patients and ethical concerns for patients receiving palliative care. We have previously reported that sex and age distribution of adult and older patients included in FYSIOPRIM were comparable to those not included, although a higher proportion of non-included patients were living in institutions and more often referred because of geriatrics/functional deterioration (14). As a result, our sample may have had better physical performance compared with the broad spectrum of patients receiving home based physiotherapy.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…Through the Research program for Physiotherapy in Primary Health Care, the FYSIOPRIM, a set of standardized methods and tools have been developed, enabling studies of clinical courses for patients receiving primary care physiotherapy (14). The present study is a longitudinal observational study of adults and older patients receiving physiotherapy, mainly home based, in Trondheim Municipality, which is located in the middle part of Norway.…”
Section: Design and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The parents of all eligible children were asked to participate prior to or during the rst consultation with the PT. A tablet application was used for electronic data collection, and parents also had the opportunity to answer questionnaires through an e-mail link (12). This study used baseline data registered by the PT and the parents separately and in collaboration and only data registered in collaboration at follow-up, due to a substantial amount of missing parent-reported data at follow-up.…”
Section: Data Collection Proceduresmentioning
confidence: 99%